Factors affecting first-grade pupils' physical activity during the school day: A pilot study - Dita Culkova; Veronika Dušková (Journal of Childhood, Education & Society, 2025)
Physical activity is essential for the healthy development of children, yet many do not achieve the recommended levels. This study investigates the influence of school environments and educational practices on pupils' PA during the school day, emphasizing the importance of supportive school conditions and structured activities. This pilot study involved 43 children from three primary schools in the Olomouc region of the Czech Republic. PA was measured using digital pedometers. Data on school conditions and family lifestyle were collected via two questionnaires. The analysis employed variance inflation factor analysis, principal component analysis (PCA), multiple linear regression, and Spearman’s correlation coefficient to identify key predictors of PA. The results show that the most influential factors on PA were passive conditions of the school environment, particularly school size and access to sports facilities. Active conditions, such as organized PA breaks and outdoor learning, also had a positive effect on PA levels. However, family lifestyle did not show a significant direct impact on school-day PA.  The findings underscore the crucial role of school environments and educational practice in maintaining children's PA. There is a significant need for policies and initiatives that promote active school environments. Schools should implement comprehensive PA programs to support children’s overall health and well-being.